The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3126/kumj.v10i1.6913
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Argyrophilic Nucleolar Organizer Region (AgNOR) Study in Cytological Evaluation of Fluids, Especially for Detection of Malignancy

Abstract: BackgroundSerous effusion smears reported as "suspicious for malignancy" pose problems in clinical management. Silver staining for argyrophilic nucleolar organizer regions (AgNOR) has proved useful in making a cytopathologic differential diagnosis between benign and malignant cells. Nucleolar organizer regions(NORs) are loops of DNA located in acrocentric chromosomes. These NORs are visualized by silver staining technique that recognizes these argyrophilia associated proteins which are increased in malignancy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Both these values were higher than that obtained by G.G Nair which was 33.56% for cell block method & 14.48% for conventional smear analysis (22) . The most common primary malignancy in the fluid samples was Serous Carcinoma Ovary (33.3%%) in the present study; similar to the studies by Karki S et al (23) , Bjorn et al (24) and…”
Section: Discussionsupporting
confidence: 82%
“…Both these values were higher than that obtained by G.G Nair which was 33.56% for cell block method & 14.48% for conventional smear analysis (22) . The most common primary malignancy in the fluid samples was Serous Carcinoma Ovary (33.3%%) in the present study; similar to the studies by Karki S et al (23) , Bjorn et al (24) and…”
Section: Discussionsupporting
confidence: 82%
“…Karki et al 34 found irregularly shaped AgNORs in malignant cells of pleural and peritoneal effusions, and large and individual AgNORs in benign cells of the same effusions. Arora et al 35 showed that apparently the number of AgNORs per nucleus in patients with SCC of the larynx increases as the degree of tumor dedifferentiation increases.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our findings are similar to those described for cancers of the larynx 35 and for cells of pleural and peritoneal effusions. 34 …”
Section: Discussionmentioning
confidence: 99%
“…AgNORs correlate with the proliferative activity of neoplasms. Increased AgNOR counts may reflect increased proliferative activity of cells [29].…”
Section: Introductionmentioning
confidence: 99%
“…AgNOR increasingly applied in histopathology research following suggestions that there may be a possible association between high AgNOR counts and malignant transformation [29]. It is interesting to hypothesize, therefore, that the numbers, the shape, and the distribution of AgNORs within the nucleus might be of potential use in predicting behavior in different carcinomas [30].…”
Section: Introductionmentioning
confidence: 99%